Crown-Gall Tumors Possess Tumor-Specific Antigenic Sites on Their Cell Walls - Galsky, Alan G. (1981)
Rabbits were injected with cell walls obtained from crown-gall tumor tissue or the corresponding cell walls from normal potato tissue. The serum obtained from rabbits 53 days after they were injected with tumor cell walls contained immunoglobins that reacted with both tumor and normal cell walls as well as with the cells from the inciting strain of Agrobacterium tumefaciens. When this serum was repeatedly absorbed against normal cell walls and the cells of the inciting strain of Agrobacterium tumefaciens, only tumor-specific immunoglobins remained. These immunoglobins did not react with cell walls obtained from meristematic (nontumorous) potato tissue. Yet this same serum reacted with crown-gall tumor cell walls obtained from turnip and carrot discs.